Measurement of azimuthal hadron asymmetries in semi-inclusive deep inelastic scattering off unpolarised nucleons - C. Adolph; R. Akhunzyanov; M.G. Alexeev; Yu. Alexandrov; G.D. Alexeev; A. Amoroso; V. Andrieux; V. Anosov; A. Austregesilo; B. Badełek; F. Balestra; J. Barth; et al. (Nuclear Physics B, 2014)
Spin-averaged asymmetries in the azimuthal distributions of positive and negative hadrons produced in deep inelastic scattering were measured using the CERN SPS longitudinally polarised muon beam at 160 GeV/c and a 6LiD target. The amplitudes of the three azimuthal modulations cos⁡ϕh, cos⁡2ϕh and sin⁡ϕh were obtained binning the data separately in each of the relevant kinematic variables x, z or pTh and binning in a three-dimensional grid of these three variables. The amplitudes of the cos⁡ϕh and cos⁡2ϕh modulations show strong kinematic dependencies both for positive and negative hadrons.